Effect of a Corrective Exercise Program Based on Scapular Stability on Upper Cross Syndrome in Wheelchair Basketball Athletes - A. Maarouf; A.A. Norasteh; H. Daneshmandi; A. Ebrahimi-Atri (Afarand Scholarly Publishing Institute, 2020)
Aims: Wheelchair basketball athletes, as a group of people with spinal cord injury, are at risk for upper cross syndrome. The purpose of the present study was to investigate the effect of a corrective exercise program based on scapular stability on upper cross syndrome in wheelchair basketball athletes. Materials & Methods: In this semi-experimental study that was conducted in 2017-2018, 24 veteran and handicapped wheelchair basketball athletes who had spinal cord injury with upper cross syndrome in Mashhad were selected by purposive sampling method and divided into control (n=12) and case (n=12) groups. A corrective exercise program based on scapular stability were administered to the case group for 8 weeks. Camera and flexible ruler tools were used to measure forward head, rounded shoulder and kyphosis, respectively. Data analysis was performed by SPSS 23 software using independent t-test, paired t-test, one-way analysis of variance, and Tukey's post hoc test. Findings: The severity of forward head, rounded shoulder and kyphosis abnormalities was less in class 3 than in class 1 and 2. There was a significant difference between the case and control groups after training in all three forward head, rounded shoulder, and kyphosis abnormalities (p<0.05). Conclusion: The corrective exercises based on scapula stability are one of the most useful training methods for restoring muscle balance and preventing and correcting abnormalities in wheelchair basketball athletes.